Strategies for Coping with Neuropathic Pain and Impact of Pain on the Functional Condition of Patients - Małgorzata Kołpa; Ewa Mężyk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Determining the strategies, which patients implement in order to fight the pain and the extent, to which they are able to control symptoms can greatly facilitate the selection of appropriate treatment. Aim. The study aimed at assessing strategies to cope with pain by patients suffering from neuropathic pain. Material and Methods. The study group consisted of 60 patients of the Pain Management Unit aged of 25–80 years suffering from neuropathic pain. The study was performed with the use of Coping Strategies Questionnaire (CSQ), Visual Analogue Scale (VAS) as well as a survey of own design. Results. The average intensity of pain in the study group was 7.88 in VAS (±1.64). The most widely used strategy for dealing with pain in the study group was Praying (av. 3.3±1.1), whereas on the second place was Catastrophizing (av. 3.1±1.6). The patients over the age of 60 are significantly more likely to apply those strategies than younger patients. The other strategies were applied above all by the patients below 60. Conclusions. The most often applied strategies in the study group was Praying and Catastrophizing. The choice of strategies for coping with pain varied depending on age, to lesser extend it was conditioned the gender. (JNNN 2016;5(1):10–15)